Jatropha (Jatropha curcas) based intercropping systems: An alternate land use for rehabilitation of degraded sodic lands - SINGH, YASH PAL; MISHRA, VINAY K; DIXIT, HIMANSHU; GUPTA, RAVINDRA K (The Indian Journal of Agricultural Sciences, 2019)
A field study was conducted to evaluate the performance of jatropha based intercropping model as an alternate land use for rehabilitation of degraded sodic lands. Cultivation of Jatropha curcas L. as monocropping has not been proven economically viable because of its late fruiting and poor yield. A small and resource poor farmer having sodic soils can't wait for at least five years to get income. Therefore, the present study was conducted to replace monoculture of jatropha with intercrops in between jatropha plantation in sodic soils to optimize land use efficiency. Study revealed that the plantation of jatropha at 3 m apart and inter- cultivation of sweet basil - matricaria cropping sequence for four years was highly economical than the planting at 3Ã—2m spacing and other tested crop rotations. Soil physicochemical and biological properties in sweet basil - matricaria with jatropha L. as main crop were better than rest of the cropping sequences evaluated. Soil microbial biomass carbon (MBC) was also higher with sweet basil-matricaria cropping sequence followed by sorghum wheat and maize-linseed. The study shows that inter cultivation of Jatropha in sodic soils encouraged biological activities in the rhizosphere. Inter-cultivation of medicinal and aromatic crops under Jatropha plantations for four years was found to be an alternate land use sequence to obtain higher income than the sole plantation of Jatropha in sodic soils. Soil health improvement due to intercropping can provide a better environment for cultivation of highly remunerative crops in future.